2012
DOI: 10.7763/ijesd.2012.v3.260
|View full text |Cite
|
Sign up to set email alerts
|

Two-Parameter Gamma-Based SUH Derivation

Abstract: Abstract-A simple procedure is suggested to compute direct runoff hydrograph (DRH) using an improved two-parameter gamma distribution (2PGD) based synthetic unit hydrograph (SUH) and it is tested on several storm events recorded in 3 different hydrometeorological catchments. When compared, the computed hydrographs were more accurate than those due to popular Gray, SCS, and Snyder methods, because of avoidance of manual, subjective, and tiresome fitting of hydrograph through few data points for their adjustment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Some of the relevant studies which are included in the References list of this manuscript will be briefly summarized in the following. Commonly, the 2-parameter gamma and the 3-parameter beta distributions are used for this purpose (e.g., Asquith et al 2005;Bhuyan et al 2015;Bhunya et al 2004Bhunya et al , 2011Ghorbani et al 2015;Haktanir and Sezen 1990;Naghibi et al 2018;Patil et al 2012;Roy and Thomas 2016;Singh 2000;Singh et al 2014). Asquith et al (2005) used measured rainfall-runoff data of 1600 storms in 93 watersheds of sizes from 0.8 to 432 km 2 in the State of Texas with the purpose of deriving synthetic unit hydrographs by four different approaches, the 2-parameter gamma distribution being one of them.…”
Section: Review Of Literature About Synthetic Unit Hydrographs As Concerns Current Studymentioning
confidence: 99%
See 3 more Smart Citations
“…Some of the relevant studies which are included in the References list of this manuscript will be briefly summarized in the following. Commonly, the 2-parameter gamma and the 3-parameter beta distributions are used for this purpose (e.g., Asquith et al 2005;Bhuyan et al 2015;Bhunya et al 2004Bhunya et al , 2011Ghorbani et al 2015;Haktanir and Sezen 1990;Naghibi et al 2018;Patil et al 2012;Roy and Thomas 2016;Singh 2000;Singh et al 2014). Asquith et al (2005) used measured rainfall-runoff data of 1600 storms in 93 watersheds of sizes from 0.8 to 432 km 2 in the State of Texas with the purpose of deriving synthetic unit hydrographs by four different approaches, the 2-parameter gamma distribution being one of them.…”
Section: Review Of Literature About Synthetic Unit Hydrographs As Concerns Current Studymentioning
confidence: 99%
“…Naghibi et al (2018) studied the goodness of the distributions of 2-parameter gamma, 3-parameter beta, chi-square, and Weibull for synthetic unit hydrographs to be fitted to 14 storms in the Bar watershed in Iran, and they concluded that the 2parameter gamma distribution was the best for their cases. Patil et al (2012) presented an analytical method for computing the parameters of the 2-parameter gamma distribution as a synthetic instantaneous unit hydrograph using the dimensionless quantity β (qp × tp). Patil et al (2012) applied the 2-parameter gamma synthetic unit hydrograph first to a very small urban watershed in Cincinnati, OH (in USA) (0.0003 km 2 ), and next to two watersheds in India, whose sizes were 0.177 km 2 and 823.6 km 2 .…”
Section: Review Of Literature About Synthetic Unit Hydrographs As Concerns Current Studymentioning
confidence: 99%
See 2 more Smart Citations